URGENSI PENELITIAN MANAJEMEN RANTAI PASOK: PEMETAAN ISU, OBJEK, DAN METODOLOGI - Sherlywati Sherlywati (Jurnal Manajemen Maranatha, 2018)
The purpose of this paper is to raise the issue of urgency of supply chain management research in terms of developmental issues, trends and challenges, as well as research objects and methologies in the any industry, business sector, and public sector. This study is an exploratory research with the aim of finding trends, developments, and challenges of current and potential supply chain management research. Data were collected from previous studies and written interviews from supply chain management experts where domiciled in several institutions in Bandung City. The findings of this study show expert opinion on the issues of supply chain management research in terms of developments, trends, and challenges, as well as the urgency of supply chain research. While, the results of the literature review from previous study, the research objects and methodologies of supply chain management research categorized into several categories that need to be concentrated for further research. Research suggestions are aimed specifically at academic, private and public sector practitioners to update and upgrade capacity, information, and knowledge about the development of supply chain management study in a sustainable manner. This paper also suggests to establish a community of supply chain management which consist of academicians, practitioners, and government in Bandung City to share informations and experiences about research and issues related to supply chain management, such as Supply Chain Indonesia (SCI) and American Production and Inventory Control Society (APICS). Keywords: Supply Chain Management, Supply Chain Management Research, Issue of Supply Chain Management